2009
DOI: 10.1016/j.midw.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of the midwife in Australia: views of women and midwives

Abstract: Objective: To research the role of midwives in Australia from the perspectives of women and midwives. This study was part of a commissioned national research project to articulate the scope of practice of Australian midwives and to develop national competency standards to assist midwives to deliver safe and competent midwifery care.Design: A multi-method approach with qualitative data collected from surveys from women and interviews with midwives. Setting: Participants represented each state and territory in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 11 publications
2
100
0
Order By: Relevance
“…Five studies used a mixed-methods approach with triangulation of data from questionnaires and interviews [36][37][38] , or collected data from literature and focus groups 39,40 . Three studies applied a qualitative design including individual interviews 41,42 or focus groups 43 .…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies used a mixed-methods approach with triangulation of data from questionnaires and interviews [36][37][38] , or collected data from literature and focus groups 39,40 . Three studies applied a qualitative design including individual interviews 41,42 or focus groups 43 .…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Woman-centered care prioritizes the woman's individual unique needs, as defined by the woman herself -assigning to the woman choice, control and continuity of care [5][6][7][8][9][10][11][12] . This concept description has resulted from consultation with women (recipients of maternity services), midwives, obstetricians and policy makers 10,13,14 but lacks a scientific theoretical foundation.…”
Section: Introductionmentioning
confidence: 99%
“…[41,42] Non-conducive work environments and job dissatisfaction affect midwives' and nurses' intention to leave the job or their career. [43,44] The study results suggested that autonomy for midwifery practice is an important factor to change practice and improve the quality of health care. After having participated in CPD, hospital midwives felt empowered to introduce innovation or change aimed to improve the quality of obstetric and neonatal care.…”
Section: Discussionmentioning
confidence: 95%
“…These findings are consistent with results from an Australian study by Homer et al, which revealed that health facilities' system of maternity care, domination of physicians, invisibility of midwifery in decision making and regulation, were the major barriers for midwives to fully enact their role in maternity services. [43] Edmondson and Walker found that in caseload midwifery…”
Section: Discussionmentioning
confidence: 99%
“…It was essential to ensure that the attributes being assessed were ones that reflected those considered desirable of a student midwife as well as upholding the University's midwifery programme philosophy (should I say what this is?). A structured literature search revealed that mothers have a definitive idea of the values and behaviour they desired from their care provider (Homer et al, 2009). These were recorded and compared to those encapsulated by the UK Nursing and Midwifery Council (2009) and International Confederation of Midwives (2011).…”
Section: Multiple Mini Interview Instrument Developmentmentioning
confidence: 99%